Pengaruh Orientasi Religius, Hardiness, dan Quality of Friendship Terhadap Kebahagiaan Santri - Nadhifah, Noor Uyun; Wahyuni, Zulfa Indira (TAZKIYA: Journal of Psychology, 2020)
AbstractHappiness is a life’s goal for everyone. It also has an important role in the educational environment, especially for individuals who live in boarding schools. Happiness could escalate student’s motivation especially in learning and indirectly influence student’s activities while staying in boarding schools. The purpose of this study is to determine whether there are influences from religious orientation (intrinsic and extrinsic), hardiness (commitment, control, and challenge), and quality of friendship (stimulating companionship, help, intimacy, reliable alliance, self validation, and emotional security) towards the happiness of santri. This research involved 240 students from boarding schools in Bandung. The sampling technique used in this study is non probability sampling. The questionnaires for measuring happiness using OHI (Oxford Happiness Inventory), religious orientation using ROS (Religious Orientation Scale), hardiness using hardiness scale (how hardy are you?), and quality of friendship using MFQ FF (Mcgrill Friendship Questionnaire - Friend’s Functions). Confirmatory Factor Analysis (CFA) was used to test the validity of each item in the questionnaire from LISREL8.7 software. While statistical testing using multiple regression analysis of SPSS 17 software. Based on the results of the data analysis, there was a significant influence of religious orientation, hardiness, and quality of friendship on students' happiness. AbstrakKebahagiaan merupakan tujuan hidup bagi semua orang. Kebahagiaan juga memiliki peran penting dalam lingkungan pendidikan khususnya bagi individu yang tinggal di pondok pesantren. Dengan adanya kebahagiaan dapat meningkatkan motivasi belajar dan secara tidak langsung dapat mempengaruhi aktivitas yang dilakukan oleh para santri selama berada di pondok pesantren. Tujuan penelitian ini adalah untuk mengetahui apakah ada pengaruh dari orientasi religius (intrinsik dan ekstrinsik), hardiness (commitment, control, dan challenge), dan quality of friendship (stimulating companionship, help, intimacy, reliable alliance, self validation, dan emotional security) terhadap kebahagiaan santri. Penelitian ini dilakukan pada 240 santri pondok pesantren modern di Bandung. Teknik pengambilan sampel yang digunakan dalam penelitian ini adalah non probability sampling. Untuk alat ukur kebahagiaan menggunakan OHI (Oxford Happiness Inventory), orientasi religius menggunakan ROS (Religious Orientation Scale), hardiness menggunakan hardiness scale (how hardy are you?), dan quality of friendship menggunakan MFQ FF (Mcgrill Friendship Questionnaire - Friend’s Functions). Uji validitas alat ukur menggunakan teknik Confirmatory Factor Analysis (CFA) dengan bantuan software LISREL8.7. Sedangkan analisis data menggunakan teknik analisis regresi berganda dengan bantuan software SPSS 17. Berdasarkan hasil analisis data, diperoleh kesimpulan penelitian ada pengaruh yang signifikan orientasi religius, hardiness, dan quality of friendship terhadap kebahagiaan santri.